Postural Stability Exercise on Static Balance in Attention Deficit/Hyperactivity Disorder (AD / HD) Children in Pradnyagama Foundation - I Putu Darmawijaya; Devi Natalia Bangun; Indah Pramita (Journal of Sustainable Development Science, 2019)
Static balance disorders are often found in children with attention deficit / hyperactivity disorder (AD / HD) which causes difficulty maintaining a position and concentration on onething. The development of balance is influenced by the maturity of specific nerve cells, experience, and environment. If this is left untrained it will certainly cause problems in thedevelopment process one of which is activities that require children to sit still or stand up. This study aims to look at postural stability exercise in improving static balance in children with attention deficit / hyperactivity disorder (AD / HD). The research is experimental with the design of one pre-test and post-test group design. Exercise is carried out three times a week for four weeks. Static balance measuring instrument with one leg stance test. Data analysis was obtained by descriptive analysis and normality test with shapiro Wilk test, and hypothesis testing was carried out by Wilcoxon test. The analysis shows that postural stability exercise increases static balance by 94.9% from the average before 9.83 and after 19.16 so that postural stability exercise is proven to improve static balance in children with attention deficit / hyperactivity disorder (AD / HD) ages 7-8 year at Pradnyagama Foundation.